2008
DOI: 10.1189/jlb.1207833
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid cell differentiation in response to calcitriol for expressionCD11bandCD14is regulated by myeloid zinc finger-1 protein downstream of phosphatidylinositol 3-kinase

Abstract: Immature cells of the mononuclear phagocyte series differentiate in response to calcitriol. This is accompanied by increased expression of both CD11b and CD14 and has been shown to be phosphatidylinositol 3-kinase (PI3K) dependent. The events downstream of PI3K that regulate mononuclear phagocyte gene expression, however, remain to be fully understood. In the present study, we show that incubation of THP-1 cells with calcitriol brings about activation of the myeloid zinc finger-1 (MZF-1) transcription factor d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 60 publications
(61 reference statements)
3
21
0
Order By: Relevance
“…Limitations in sensitivity precluded quantification of early changes in CD14 and CD11b protein levels, even when immunoblots contained 75 µg of cell protein. Previous reports using FACS analysis to quantify 1,25-D3-induced expression of CD14 and CD11b in THP-1 cells have shown that CD14 protein levels markedly increased within 6 h of 1,25-D3 treatment [45] and after 72 h the reported overall increase in protein expression of CD14 and CD11b (>60- and 10-fold, respectively, [39]) are consistent with the increased mRNA pool sizes seen here. These data suggest that 1,25-D3-induced early phase responses do not affect the constitutive transcriptional activity of the CD55 promoter.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Limitations in sensitivity precluded quantification of early changes in CD14 and CD11b protein levels, even when immunoblots contained 75 µg of cell protein. Previous reports using FACS analysis to quantify 1,25-D3-induced expression of CD14 and CD11b in THP-1 cells have shown that CD14 protein levels markedly increased within 6 h of 1,25-D3 treatment [45] and after 72 h the reported overall increase in protein expression of CD14 and CD11b (>60- and 10-fold, respectively, [39]) are consistent with the increased mRNA pool sizes seen here. These data suggest that 1,25-D3-induced early phase responses do not affect the constitutive transcriptional activity of the CD55 promoter.…”
Section: Resultssupporting
confidence: 91%
“…While the major thrust of our work was to investigate the regulated expression of CD55, we uncovered unanticipated features of CD14 and CD11b that are worth noting. First, as expected, both LPS and 1,25-D3 induced increases in CD14 and CD11b and the increase in mRNA pools correlated qualitatively with the protein expression shown herein and with previously reported flow cytometry analyses [39]. However, following 1,25-D3 pretreatment, LPS promoted a coordinated control mechanism that differentially regulated CD14 and CD11b mRNA and protein pools.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Maturation of THP-1 cells by cell-free media was further monitored by the expression of CD14 antigen and by expression of the β2 integrin component, CD11b, both of which are upregulated when this promonocytic cell line differentiates into mature monocyte/macrophage-like cells [45]. Incubation of THP-1 cells with cell-free media from mock-treated PBMCs resulted in 15.4% of cells expressing CD11b while incubation with cell-free media from either Astragalus- or PMA-treated PBMCs resulted in 28.5% or 28.6%, respectively, of cells expressing CD11b.…”
Section: Resultsmentioning
confidence: 99%
“…Examples include: the induction of activator protein-1 markers of colonic epithelial cell differentiation such as activator protein-1 by protein kinase C-alpha and c-Jun N-terminal kinase-dependent mechanisms in Caco-2 colon cancer cells (Chen et al, 1999); activation of catenin adhesion proteins in MDA-MB-453 and MDA-MB-468 breast cancer cells (Pendás-Franco et al, 2007), the induction of terminal differentiation of human myeloid leukaemia cells U937 into monocytes and macrophages by activation of p21 protein (Liu M et al, 1996); and in the prostate cancer cell line LNCaP increased expression of prostate-specific antigen (Beer et al, 2006) and E-cadherin (Ortel et al, 2002). Cell type-specific prodifferentiation mechanisms include the regulation of β-catenin, PI3K signalling pathways, as well as the regulation of the activity of transcription factors such as CCAAT/enhancerbinding protein (Deeb et al, 2007;Ji and Studzinski, 2004;Moeenrezakhanlou et al, 2008;Palmer et al, 2001).…”
Section: Differentiationmentioning
confidence: 98%